A cross-sectional assessment of the prevalence and burden of mild asthma in urban China using the 2010, 2012, and 2013 China National Health and Wellness Surveys. (3rd July 2017) - Ding, Bo; DiBonaventura, Marco; Karlsson, Niklas; Ling, Xia
ABSTRACT: Objective : To estimate the prevalence of mild asthma in urban China and to measure the association between asthma severity and quality of life (QOL), work productivity, and healthcare resource use. Methods : Data were from the China National Health and Wellness Surveys (NHWS) conducted between 2010 and 2013 ( N = 59, 935), Internet-based surveys of adults in urban China. Patients were categorized by asthma severity according to self-report and Global Initiative for Asthma (GINA2014) guidelines via self-reported medication use (mild [GINA 1-2] vs moderate/severe [GINA 3-4]). Propensity scores were used to identify matched controls without asthma. These three groups (mild vs. moderate/severe vs. matched control) were compared with respect to QOL (revised Short Form-12/36), work productivity (WPAI questionnaire), and healthcare use using generalized linear models. Results : 1, 191 respondents reported an asthma diagnosis (1.99%). Then 455 (0.77% and 76.86% of the total sample and asthma sample which could be categorized based on GINA2014 guidelines, respectively) and 897 (1.50% and 75.31% of the total and asthma sample, respectively) had mild asthma based on GINA2014 guidelines and self-report, respectively. Compared with matched controls, mild patients based on GINA2014 guidelines reported worse QOL (Physical Component Summary = 44.67 vs. 48.97), more overall work impairment (54.51% vs. 34.35%), and more all-cause emergency room visits in the past 6 months (1.95 vs. 0.63 visits) (all p <.05). Similar results were observed using self-reported severity. Conclusions : Most patients with asthma in the China NHWS are mild according to either definition. Asthma patients experience significant burden to QOL, work productivity, activity impairment, and healthcare resource use.